Pengaruh Penggunaan SIA dan TI Terhadap Kinerja Individual dengan Kemampuan Teknik Pemakai sebagai Pemoderasi - Rahayu, Putu Maya Fransisca; Dharma Suputra, I Dewa Gede (E-Jurnal Akuntansi; Vol 26 No 1 (2019), 2019)
The study at 40 cooperation in the city of denpasar with 93 respondents. The technique of determination sampling method is used purposive with the questionnaire. The analysis using moderating regression analysis technique ( mra ) found results that prove the variable the use of accounting information system has positive effects and not significant on the performance of individual and information technology had a positive impact on the performance of individual .The ability of users variable technique can be moderating the influence of the use of accounting information system on the performance of individual and on the next outcome, technique variable the ability of users cannot be moderating the influence of information technology on the performance of individually on cooperation in  Denpasar. Keywords : technical ability, the use of accounting information system, the use of information technology, individual performance.